PEMILIHAN SUBJEK, POPULASI, DAN SAMPEL DAN RELEVANSINYA BAGI PENGEMBANGAN PENDIDIKAN AGAMA ISLAM - Agung Nugroho; Nuril Huda; Dina Hermina (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This conceptual article examines the fundamental concepts of research subjects, population, and sampling, and their significance for the development of Islamic Education (PAI). These methodological components are often misunderstood, resulting in inaccurate research design, biased data, and weak generalization in educational studies. Through a critical analysis of classical and contemporary methodological literature, this article clarifies the nature of research subjects, the types and functions of populations, and the various sampling techniques that influence the scientific validity of academic work. The discussion demonstrates that the accurate determination of subjects, population, and samples is not merely technical but serves as an epistemological foundation that shapes the quality of interpretation and reliability of scholarly findings. In the context of Islamic Education, these methodological elements have strategic importance, especially in addressing contemporary challenges such as digital learning, data security, media ethics, and the promotion of religious moderation in the Society 5.0 era. This article emphasizes that strong methodological literacy enables researchers to produce academic work that is more representative, adaptive, and relevant to the theoretical and practical advancement of Islamic education.